Thermopower peculiarities in thin bismuth wires - Condrea, Elena (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2011)
The resistance and thermoelectric power of pure bismuth wires are measured in longitudinal magnetic fields up to B = 14 T at temperatures between 4.2 and 25 K. At B = 0, the 200-nm samples exhibit large values of thermopower, which are dominated by diffusion with no phonon drag being evident. Both the magnetoresistance and magnetothermopower show well-pronounced features generated by the diffuse surface scattering of hole carriers. In particular, the magnetothermopower offers the possibility of identifying the characteristic magnetic field, where the diameter of the hole Larmor orbit equals the wire diameter as an extremum. The contribution of holes to the charge transport in pure Bi nanowires is more significant than generally thought. The results highlight the important role played by domination of hole carriers in the conductibility of Bi wires at low temperatures.